IMPOLITNESS in the 2024 INDONESIAN PRESIDENTIAL and VICE PRESODENTIAL CANDIDATE DEBATE: SOCIOPRAGMATIC STUDY - Kamhar, Muhammad Yusi; Laksono, Kisyani; Mulyono, Mulyono; Suhartono, Suhartono (Proceedings of International Conference on Islamic Civilization and Humanities, 2024)
This paper analyzes various strategies of impoliteness in the debates of the presidential and vice-presidential candidates in Indonesia for the year 2024 using a Sociopragmatic approach. The research aims to explore various forms of violations of politeness maxims according to Leech’s theory, such as the maxim of tact, the maxim of approbation, the maxim of modesty, the maxim of agreement, and the maxim of sympathy. The method employed in this research is descriptive qualitative method with data collection techniques through documentation. Data analysis is conducted by examining, interpreting, and analyzing the manifestations of linguistic impoliteness in the debates of presidential and vice-presidential candidates in 2024. The research findings indicate violations of all three politeness maxims in these interactions. This article recommends further research development on the six maxims within Leech’s politeness theory. These findings are expected to contribute to the advancement of linguistics as a field and provide valuable insights for policymakers, political practitioners, and the general public.